Effect of boosting system architecture and thermomechanical limits on diesel engine performance: Part II—transient operation. (October 2018) - Galindo, José; Climent, Hector; Varnier, Olivier; Patil, Chaitanya
Nowadays, internal combustion engine developments are focused on efficiency optimization and emission reduction. Increasing focus on world harmonized ways to determine the performance and emissions on Worldwide harmonized Light vehicles Test Procedure cycles, it is essential to optimize the engines for transient operations. To achieve these objectives, the downsized or downspeeded engines are required, which can reduce fuel consumption and pollutant emissions. However, these technologies ask for efficient charging systems. This article consists of the study of different boosting architectures (single stage and two stage) with a combination of different charging systems like superchargers and e-boosters. A parametric study has been carried out with a zero-dimensional engine model to analyze and compare different architectures on the different engine displacements. The impact of thermomechanical limits, turbo sizes and other engine development option characterizations is proposed to improve fuel consumption, maximum power and performance of the downsized/downspeeded diesel engines during the transient operations.